Aukus - Plevnik, Mihael (Vojaškošolski zbornik, 2024)
The defence and security alliance between Australia, the United Kingdom and the United States (AUKUS) aims to strengthen security and defence in the Indo-Pacific region through the exchange of advanced technology, including nuclear-powered submarines. Its member states respond to geostrategic tensions, in particular due to the growing influence of China, by promoting cooperation and interoperability. The partnership is based on shared values of freedom, human rights and the rule of law, and represents a strategic twist in the dynamics of global defence. AUKUS represents an important shift in international alliances, emphasizing technological superiority and strategic cooperation. Its establishment marks a crucial moment in adapting to a changing geopolitical landscape, underlining the importance of technological advances and international cooperation in maintaining global security and stability.
Keywords: Aukus; geopolitics; geopolitika; indijsko-pacifiška regija; Indo-Pacific region; Mednarodne organizacije; Mednarodni odnosi; partnership; partnerstvo; Regionalizem (mednarodna skupnost); technology; tehnologija; Vojaška politika